Post-Cold War autocratization: trends and patterns of regime change opposite to democratization. (14th May 2019) - Cassani, Andrea; Tomini, Luca
Abstract: The so-called third wave of democratization is over and scholars are increasingly alert to the apparently growing number of regime changes in the opposite direction. However, there is little agreement concerning how many distinct forms these processes can take, and even less systematic cross-regional analysis of the phenomenon, which diminishes our ability to seize its actual import. Accordingly, this article pursues a twofold goal. First, we present a framework for the analysis of the processes opposite to democratization. Specifically, we build on the notion of 'autocratization', identify similarities and differences between the various forms it can take, and catalogue how it can happen. Second, we provide new data on post-Cold War cases across the world and use these data to map the prevailing trends. The analysis confirms the increasing empirical relevance of the phenomenon, and reveals the existence of a few geographical and historical patterns in the forms and modes of contemporary autocratization.